The characteristics of stability test using Bantak as the main aggregate - Mohamad Aqif; Md. Masudul Haque; Wasiu Akande Ahmad (Journal of Engineering and Applied Technology, 2021)
This study aims to determine the characteristics of the stability test using Bantak as the main material. Fundamental studies in terms of the characteristics of Stability values include Density (Density), Flow (melting), VIM (Void in Mix), VMA (Void in Mineral Aggregate), VFB (Void Filled Bitumen), and Marshall Quotient (MQ). This study uses an experimental test method consisting of different bitumen content variants, respectively, 5%, 5.5%, 6%, 6.5%, and 7%. Each variant consists of three samples of the test object. The research was carried out at the building materials laboratory, Faculty of Engineering, Universitas Negeri Yogyakarta. The implementation stages include inspection of AC 60/70, an inspection of aggregates (fine aggregate and coarse aggregate), an inspection of fillers, and manufacturing mixed specimens and stability tests with various characteristics. The results of the research showed that the average value of stability, density, flow, void in the mix, void mineral aggregate, void filled bitumen, and Marshall quotient was 1156.44 kg, 2.33 gr/cc, 3.07 mm, 5.20 %, 13.92% 60.10% and 377.28 kg/mm. Finally, Bantak aggregate can be used as an alternative in the manufacture of hot asphalt mixtures because the research performance data meet the requirements for accepting Indonesian national standards. Its abundant availability makes Bantak a solution in exploiting Merapi material, which is very influential on the environmental impact and improves residents' economy in the quarry area.